Digital protectionism? Antitrust, data protection, and the EU/US transatlantic rift. (12th September 2018) - Lancieri, Filippo Maria
Abstract: EU authorities increasingly take antitrust and data protection enforcement action against US internet companies. While many believe in digital protectionism, this article looks at the foundations of data protection and antitrust policies across the Atlantic to propose an alternative explanation based on the distinct views over how online markets work and should be regulated. Europeans associate data protection with inalienable rights, Americans treat data as an asset. Europeans use competition policy to advance personal freedom, US antitrust policy focuses on economic efficiency. These singular EU traits encourage the regulation of major internet companies. While the European mistrust of data amassing by private parties supplies political motivation to rein in on digital giants, its competition law framework provides a toolkit capable of overcoming challenges commonly present whenever regulators take antitrust enforcement action against Big Data firms. The US does not share either. This indicates that the EU/US divide over internet regulation will grow—and transatlantic tensions perilously increase. The article concludes by arguing for an adjusted role for economic reasoning in antitrust enforcement as a way to bridge differences.